Prenatal and postnatal presentation of PRMT7 related syndrome: Expanding the phenotypic manifestations. Issue 1 (4th December 2018) - Birnbaum, Roee; Yosha‐Orpaz, Naama; Yanoov‐Sharav, Miri; Kidron, Dvora; Gur, Hila; Yosovich, Keren; Lerman‐Sagie, Tally; Malinger, Gustavo; Lev, Dorit
Abstract : Protein arginine methyltransferase 7 ( PRMT7 ) is a member of a family of enzymes that catalyze the transfer of methyl groups from S‐adenosyl‐l ‐methionine to nitrogen atoms on arginine residues. Arginine methylation is involved in multiple biological processes, such as signal transduction, mRNA splicing, transcriptional control, DNA repair, and protein translocation. Currently, 10 patients have been described with mutations in PRMT7 . The shared findings include: hypotonia, intellectual disability, short stature, brachydactyly, and mild dysmorphic features. We describe the prenatal, postnatal, and pathological findings in two male sibs homozygote for a mutation in PRMT7 . Both had intrauterine growth restriction involving mainly the long bones. In addition, eye tumor was found in the first patient, and nonspecific brain calcifications and a systemic venous anomaly in the second. The pregnancy of the first child was terminated and we describe the autopsy findings. The second child had postnatal growth restriction of prenatal onset, hypotonia, strabismus, sensorineural hearing loss, genitourinary and skeletal involvement, and global developmental delay. He had dysmorphic features that included frontal bossing, upslanting palpebral fissures, small nose with depressed nasal bridge, and pectus excavatum. Our patients provide additional clinical and pathological data and expand the phenotypic manifestations associated with PRMT7 homozygote/compound heterozygote mutations to include brain calcifications and delayed myelination, and congenital orbital tumor.